Flexural behaviour of a new lightweight glass fibre-reinforced polymer–metal string bridge with a box-truss composite girder. Issue 1 (January 2020) - Mao, Haifeng; Zhang, Dongdong; Chen, Li; Zhao, Qilin; Su, Xiaoping; Yuan, Jiaxin
A new glass fibre-reinforced polymer–metal structure with a string box-truss girder was designed as a vehicular emergency bridge. The glass fibre-reinforced polymer–metal emergency bridge is intended to be lightweight, structurally sound, with a long span and modular feasibility, and associated with a faster construction bridging system. In this study, the detailed conceptual design of the new bridge is described first. A large-scale static bending loading test was carried out on a fabricated bridge to examine its actual flexural performance under the serviceability limit state. The experimental emergency bridge exhibited a satisfactory overall stiffness and loading-carrying capacity in terms of its intended applications. Its linear-elastic flexural behaviour implies that the structural design of such a unique emergency bridge subjected to positive flexural moment is stiffness-driven instead of strength-driven. Furthermore, structural computational models, including three-dimensional finite element models and a simplified analytical planar model, were constructed and validated by comparing with the experimental results. The elicited comparisons indicated that the realistic nodal stiffness of the hybrid pre-tightened teeth connection and its adjacent steel planar gusset plates ought to be considered in numerical and analytical modelling. Correspondingly, during the preliminary design phase and calculations, the flexural behaviour of this unique emergency bridge can be predicted using the validated numerical and simplified analytical models.